Unique Clinical and Histological Features of Placental Mesenchymal Dysplasia Complicated by Severe Preeclampsia in the Midtrimester - Yoshimitsu Kuwabara; Mirei Yonezawa; Yumene Kubota; Tomoko Ichikawa; Ryuji Ohashi; Toshiyuki Takeshita (American Journal of Perinatology Reports, 2020)
Detailed clinical and pathological features of placental mesenchymal dysplasia (PMD) complicated by preeclampsia (PE) are unknown. A 39-year-old nulliparous woman was referred at 19 weeks gestation. Ultrasound examination identified a fetus with severe growth restriction (−2.8 SD) and a markedly thickened placenta with many cystic structures suggestive of PMD. At 21 weeks, the patient developed severe hypertension (180/95 mm Hg) with marked proteinuria and an elevated serum soluble fms-like tyrosine-kinase-1 (sFlt-1) level (47,000 pg/L). The pregnancy was terminated to protect maternal health. Placental weight was 450 g and no histopathological findings of either proliferation or dysplasia were observed in the trophoblast. Villous chromosome examination revealed a 46XX karyotype, consistent with the diagnosis of PMD. In addition to the pathological findings of vascular endothelial dysfunction characteristic of the placenta in PE cases, enhanced expression of sFlt-1 in the syncytiotrophoblast of the enlarged villi was confirmed by immunohistochemistry as a novel finding in this condition. Monitoring of the serum sFlt-1 value is suggested to be a useful predictor of the pathological change associated with extremely early severe PE in PMD cases.